Insulin Resistance, Inflammation, and Obesity: Role of Monocyte Chemoattractant Protein-1 (orCCL2) in the Regulation of Metabolism - Anna Rull; Jordi Camps; Carlos Alonso-Villaverde; Jorge Joven (Mediators of Inflammation)
To maintain homeostasis under diverse metabolic conditions, it is necessary to coordinate nutrient-sensing pathways with the immune response. This coordination requires a complex relationship between cells, hormones, and cytokines in which inflammatory and metabolic pathways are convergent at multiple levels. Recruitment of macrophages to metabolically compromised tissue is a primary event in which chemokines play a crucial role. However, chemokines may also transmit cell signals that generate multiple responses, most unrelated to chemotaxis, that are involved in different biological processes. We have reviewed the evidence showing that monocyte chemoattractant protein-1 (MCP-1 or CCL2) may have a systemic role in the regulation of metabolism that sometimes is not necessarily linked to the traffic of inflammatory cells to susceptible tissues. Main topics cover the relationship between MCP-1/CCL2, insulin resistance, inflammation, obesity, and related metabolic disturbances.